Impact of engineering parameters on performance of relay-assisted network - Issam Maaz; Jean-Marc Conrat; Jean-Christophe Cousin; Samer Alabed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper compares the performance of a relay assisted network to the performance given by a classical macrocell network without the presence of relay node schemes. The capacity enhancement provided by a relaying system as a function of the relay antenna height and the propagation environment surrounding the relay nodes is analyzed and discussed in details. The analysis in this work is based on the theoretical Shannon capacity where both measured/experimental path loss and calibrated path loss models are taken into consideration. In this work, we assume a decode and forward scheme, a full-duplex relaying protocol and an optimized relay location is investigated. A 30 % of improvement in the macrocell capacity is achieved with the usage of relaying scenario compared to a classical macrocell network. Furthermore, increasing the relay antenna height from 4 meters to 12 meters can significantly increase the relay capacity to more than 20 % in suburban and moderate urban environments.